ANALISIS KEJADIAN GIZI KURANG PADA BADUTA USIA 6-24 BULAN - Adibin Adibin; Wa Ode Salma; Nani Yuniar (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Nutritional status is one indicator of children's health. The five-year period (toddler age) is an important period in which children need adequate nutrition to support their physical growth. This study aims to analyze factors related to the nutritional status of children aged 6-24 months in the working area of ​​the Health Office of North Buton Regency. This cross sectional study was conducted in the working area of ​​the North Buton District Health Office in June-July 2022 involving 105 children and mothers. The research data were analyzed using the chi square test. The results showed that the nutritional status of the majority was good as many as 75 children (71.4%), followed by the less category as many as 30 children (28.6%). Nutritional status is related to family income (P-value < 0.000), knowledge (P-value < 0.000), parenting style (P-value < 0.000). The conclusion of the study is that poor nutritional status will have an impact on the quality of under-fives and nutritional status can be prevented by a good understanding of the mother about nutrition, the family is able to provide nutritious food, the baby is exclusively breastfed until the age of 6 months, parenting is oriented towards growth and development. clown.